Analysis of the role of the TRIZ Model and the TOD concept of changes in urban mass transportation towards comfort of life (Case study around Soekarno Hatta Airport Tangerang, Banten) - Kurniawan, Johanes kurniawan.L; Samosir, Johar; Hutaurukt, Paul; Rahman Achmad, Nasirur; Mizan, Mizan; Nurhakim, Nurhakim (Dinasti International Journal of Economics, Finance & Accounting, 2025)
The purpose of this study is to analyze the extent of the role of the TRIZ (Theory of Incentive Solving) Model to the negative impact of gentrification of urban changes around Soekarno Hatta Airport Tangerang, Banten, with the concept of Mixed Use Building and the concept of TOD (Transit Oriented Development) can overcome the comfort of living in the suburbs around Soekarno Hatta Airport Tangerang, Banten, especially the area of 5 sub-districts, namely Benda, Kosambi, Neglasari, Rawabokor, and Teluk Naga sub-districts, where the poorest of the three sub-districts are Pakuhaji, Teluknaga, and Kosambi. there has not been much attention from the academic community, so this is a concern to be used as an object of research. The realization of this development concept usually utilizes existing infrastructure, optimizes the use of Mass Transportation networks and increases Community Mobility at the local level. The TOD concept is applied by combining residential areas, shops, offices, open spaces and public facilities within a comfortable walking distance. . it is known that the adjusted R Square value is 0.704, this means that the simultaneous influence of variables X1 and X2 on variable Y is 70.4%, the remaining 29.6% is influenced by other factors.